2022
DOI: 10.3390/fermentation8110625
|View full text |Cite
|
Sign up to set email alerts
|

Biological Potential of Alternative Kombucha Beverages Fermented on Essential Oil Distillation By-Products

Abstract: The complete waste streams (solid waste residue, wastewater, and hydrolate) from the essential oil production of basil, chamomile, lavender, rosemary, and hyssop plants were used as a cultivation media for fermentations of a health-beneficial beverage called kombucha. Considering that these waste streams have not been used as a medium for obtaining kombucha, the main focus of this study was on the biological profiling and sensory analysis of newly-obtained kombucha beverages. According to fermentation paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Although Ranitović et al. (2022) reported an increase in TPC of the kombucha prepared from the essential oil distillation byproducts, they found that TFC was decreased, which is similar to our findings. Another study conducted by Vitas et al.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Although Ranitović et al. (2022) reported an increase in TPC of the kombucha prepared from the essential oil distillation byproducts, they found that TFC was decreased, which is similar to our findings. Another study conducted by Vitas et al.…”
Section: Resultssupporting
confidence: 91%
“…This result may be attributed to the degradation of large molecular polyphenols in the tea into smaller polyphenol monomers or the conversion of insoluble bound polyphenols into soluble free polyphenols by the enzymes produced by the microorganisms during the fermentation process (Candra et al, 2023;Jafari et al, 2020;Khosravi et al, 2019;Wang et al, 2022). Although Ranitović et al (2022) reported an increase in TPC of the kombucha prepared from the essential oil distillation byproducts, they found that TFC was decreased, which is similar to our findings. Another study conducted by Vitas et al (2018) also demonstrated that the TFC of yarrow was decreased after fermentation.…”
Section: Total Phenolic and Total Flavonoid Contents And Phytochemica...supporting
confidence: 88%
“…Figure 6 shows these distances for each sample for all assessors, enabling the identification of the assessor's sensory score distance from the consensus. If the Euclidean distance is lower, the assessor is closer to the consensus [33]. According to the presented results, assessor 2 exerts the most elevated distance from the consensus for essential oil evaluation.…”
Section: Sensory Analysismentioning
confidence: 71%
“…For pharmaceutical activities of different sweet potato extracts, anti-inflammatory (AIA) and anti-hyperglycemic (AHgA) activities were utilized as in detail explained in the study of Ranitović et al [ 22 ]. Percentages of inhibitory activities were calculated using absorbances obtained from a microtiter plate reader (Thermo Fisher Scientific Inc., Waltham, MA, USA) of samples and their controls at the concentration of 50 mg/mL for all extracts.…”
Section: Methodsmentioning
confidence: 99%